Dioctadecyldimethylammonium bromide vesicles prepared by the surfactant removal method - Feitosa, E.; Karlsson, G. (Elsevier B.V., 2006)
Dioctadecyldimethylammonium bromide (DODAB) is a double chain vesicle-forming cationic surfactant, whereas octa-ethyleneglycol mono-n-dodecyl ether (C12E8) is a single chain micelle-forming nonionic surfactant. At room temperature (ca. 22 degrees C) C12E8 molecules self-assemble in water as micelles while DODAB is insoluble. A mixture of DODAB and C12E8, however, can be soluble in water at room temperature depending on the relative amount of the compounds. We report the formation of small unilamellar vesicles (SUVs) by dialyzing at room temperature a mixture of 1.0 mM DODAB with 10 mM C12E8 in water. Extended bilayers are formed as well in equilibrium with vesicles. Such structures are viewed by a cryogenic transmission electron microscopy (cryo-TEM) image. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Cationic vesicle; mixed micelles; surfactant removal method; dioctadecyldimethylammonium bromide; octa-ethyleneglycol mono-n-dodecyl ether; Cryo-TEM